Case Report: “I got my brain back” A patient’s experience with music-induced analgesia for chronic pain - Mercadillo, Roberto E.; Garza-Villarreal, Eduardo A. (Frontiers in Psychology, 2023)
Listening to music has progressively been proposed as a complementary alternative for chronic pain; understanding its properties and its neurobiological bases is urgent. We show a phenomenological investigation of a woman who has lived 20 years with chronic pain. The inquiry involved her experience of the context in which she listens to music, the intensity and quality of pain, body mapping, memories, emotions, and cognition. The participant listens to music for different reasons, such as pain and anxiety relief, motivation to exercise and quality of sleep, among others, but all seem to revolve around different strategies for pain management. Experiences in physiological and cognitive aspects included perceived restorative sleep that may have improved the participant's general well-being and improved cognitive and motor performance as well as communication skills. The music enabled the participant not only to relieve pain but also withdrawal effects after discontinuing her opioid-based treatment. These effects may encompass endogenous opioid and dopamine mechanisms involving natural analgesia associated with pleasurable experiences. Future studies could consider phenomenological case studies and therapeutic accompaniment to reorient subjective properties of pain, and expand quantitative and qualitative knowledge for more comprehensive reports on music and analgesia.